Batik sales product recommendation system on E-Commerce Website using FP-Growth Algorithm - Foster, Bob; Deni Johansyah, Muhammad (Opción, 2020)
The study aims to investigate the Batik sales product recommendation system on E-Commerce Website using the FP-Growth Algorithm. In this case, the sale of batik cloth is website-based. The website system is made in the PHP programming language. As a result, the process of implementing product recommendations that can be categorized as a best seller product, the product will appear directly on the main page of the website, product recommendations will change according to needs. From this research, it can be concluded that the application of a product recommendation system on e-commerce websites selling batik can be implemented.